Evaluation of osteoconduction of a synthetic hydroxyapatite/β-tricalcium phosphate block fixed in rabbit mandibles - Pires, Luis Carlos de Almeida; da Silva, Rodrigo Capalbo [UNESP]; Poli, Pier Paolo; Esgalha, Fernando Ruas; Hadad, Henrique [UNESP]; Palin, Letícia Pitol [UNESP]; Santos, Ana Flávia Piquera [UNESP]; Colombo, Luara Teixiera [UNESP]; de Jesus, Laís Kawamata [UNESP]; Bassi, Ana Paula Farnezi [UNESP]; Maiorana, Carlo; Okamoto, Roberta [UNESP]; et al. (MDPI, 2020)
(1) Background: This study aimed to evaluate the incorporation of hydroxyapatite/β-tricalcium phosphate blocks grafted in rabbit mandibles. (2) Methods: Topographic characterization of biomaterial was performed through scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDX). Ten rabbits randomly received autogenous bone graft harvested from the tibia (Autogenous Group—AG) or synthetic biomaterial manufactured in β-tricalcium phosphate (Biomaterial Group—BG) at their right and left mandibular angles. Euthanasia was performed at 30 and 60 postoperative days; (3) Results: SEM-EDX showed a surface with the formation of crystals clusters. Histological analyses in BG at 30 days showed a slower process of incorporation than AG. At 60 days, BG showed remnants of biomaterial enveloped by bone tissue in the anabolic modeling phase. Histometric analysis showed that mean values of newly formed bone-like tissue in the AG (6.56%/9.70%) were statistically higher compared to BG (3.14%/6.43%) in both periods, respectively. Immunohistochemical analysis demonstrated early bone formation and maturation in the AG with more intense osteopontin and osteocalcin staining. (4) Conclusions: The biomaterial proved to be a possible bone substitute, being incorporated into the receiving bed; however, it showed delayed bone incorporation compared to autogenous bone.
Keywords: Biocompatibility; Biomaterials; Bone augmentation; Bone conduction; Bone grafting; Calcium hydroxyapatite; Tissue regeneration